Una mirada a la argumentación jurídica desde la lógica aristotélica - Fernández Ruiz, Graciela (2014)
The aim of this paper is to show how the aristotelian view about logic and argumentation can be useful in the study of legal argu- mentation. In his logical works –which were later grouped together under the title Organon or ‘instrument for rational thinking’–. Aristotle studies many kinds of argumentation: from demonstrative arguments to rhetorical argumentation and even fallacies. Nowadays, when analyzing actual Legal Rulings, it can be found that the argumentative practices showed there reflect a blending of analytical, dialectical and rhetorical devices, thus showing examples of all the logical machinery described by Aristotle in his Organon.